User's satisfaction towards Perpustakaan Sultan Badlishah (PSB) among Bachelor (Hons.) in Library Science and Information Management (BIS) students in UiTM Kedah / Siti Nur Bashirah Abd Razak - Abd Razak, Siti Nur Bashirah (2010)
The purpose of this study is to investigate user satisfaction towards PSB library portal from the perspective of Bachelor in Library Science and Information Management (BIS) student's in UiTM Kedah. The study is survey based on 132 questionnaires that were sent out to BIS students in UiTM Kedah. In terms of information quality assessment, respondents had indicated that the library portal met their expectations. All the information quality attributes, namely currency, accurate, important, timely, reliable and updated information were rated highly by users. Equally to information quality is systems quality and user interface design. This study utilizes effective methods to determine user's satisfaction towards library portal. It provides a study of only one portal, however and as such the results are indicative only of the views of one group of students using portal. This study offers opinions of user's satisfaction towards library portal and would be of value to digital library researcher, or others interested in user's satisfaction towards library portal or interface design.